FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN DIET PASIEN HIPERTENSI DI BAGIAN RAWAT JALAN DI RSUD PROF. DR. H. ALOEI SABOE GORONTALO - Muh. Isman Jusuf; Salahuddin Liputo (-, 2021)
Hypertension is persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. Hypertensive patients require good treatments. One of the them is diet management. The purpose of this study was to determine the factors that influence dietary adherence in hypertensive patients at Prof. Dr.H. Aloei Saboe Hospital, Gorontalo city. This study was an analytic study with a cross-sectional study approach. Data were analyzed by univariate and bivariate (chi-square). The results of study showed that gender, age, education and disease severity effect on dietary adherence in hypertensive patients at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. Thus researcher provided advice to patients with hypertension, that they should improve self-adherent to perform the diet for hypertension. And to hospital, they should be able to improve the quality of care and giving information about diet to the hypertensive patients. The researcher also advised the Health Office to arrange the programs related to increase of dietary adherence of hypertension.